The executive bodies as subjects of public administration: concepts, signs, types and their reforming - Гнатовська, Альона Ільдусівна; Гнатовська, А. І.; Гнатовская, Алена Ильдусовна; Hnatovska, Alona I. (Riga : Izdevniecība “Baltija Publishing”, 2020)
The article is devoted to the study of the views of scientists on the definition of «executive bodies». Features of executive bodies are outlined. The opinions of scientists on the features that are inherent in the executive branch are also described. The system of executive bodies is analyzed and the peculiarity of each level of executive bodies is determined.The article describes the stages of reforming the executive branch in independent Ukraine. The normative-legal acts that introduced the reform of executive bodies have been studied and the problems that need to be solved have been identified.

Стаття присвячена дослідженню поглядів науковців на визначення поняття «органи виконавчої влади». Окреслено особливості діяльності органів виконавчої влади. Описано також думки вчених щодо особливостей, які притаманні виконавчій владі. Проаналізовано систему органів виконавчої влади та визначено особливості кожного рівня органів виконавчої влади. У статті описано етапи реформування виконавчої влади в незалежній Україні. Досліджено нормативно-правові акти, які запровадили реформу органів виконавчої влади, визначено проблеми, які потребують вирішення.
Hnatovska A. І. The executive bodies as subjects of public administration: concepts, signs, types and their reforming / A. I. Hnatovska // Public administration under modern conditions: concept, features, challenges : Collective monograph. - Riga : Izdevniecība “Baltija Publishing”, 2020. - P. 65-81.
Keywords: executive branch; central executive bodies; public administration; виконавча влада; центральні органи виконавчої влади; державне управління; Research Subject Categories::LAW/JURISPRUDENCE::Public law